Prevalence, bio-serotype, antibiotic susceptibility and genotype of Yersinia enterocolitica and other Yersinia species isolated from retail and processed meats in Shaanxi Province, China. (1st October 2022) - Lü, Zexun; Su, Xiumin; Chen, Jin; Qin, Mingqian; Sheng, Huanjing; Zhang, Qian; Zhang, Jinlei; Yang, Jun; Cui, Shenghui; Li, Fengqin; Feng, Chengqian; Peng, Zixin; et al.
Abstract: This study characterized Yersinia enterocolitica and other Yersinia spp. isolated from retail and processed meats sampled in Yangling, Shaanxi Province, China (2018–2019). The detection rate of Yersinia -positive samples was 14.30% (86/600). Yersinia was commonly prevalent in beefs (32.00%), frozen meats (25.00%), packaged meats (21.65%), and meats from supermarkets (17.23%). Y. enterocolitica was identified as the most prevalent species (50.00%, 62/124), followed by Y. frederiksenii (24.19%), Y. intermedia (16.94%), and Y. kristensenii (8.87%). Most Y. enterocolitica isolates were of bio-serotype 1A/nt (67.74%). Sixty-three isolates (50.81%) carried yst B and two isolates (1.61%) carried rfb C. Yersinia isolates were commonly resistant to ampicillin (91.94%), cefazolin (71.77%), amoxicillin/clavulanic acid (56.45%), cefoxitin (28.23%), and trimethoprim/sulfamethoxazole (1.61%). Sixty-six isolates (53.23%) were resistant to three or more antibiotics. Pulse field gel electrophoresis analysis revealed that the genetic homology of Yersinia isolates between pork, beef, and chicken was low, as was that of biotype 1A isolates. The results indicate that Y. enterocolitica and other Yersinia spp. (especially bio-serotype 1A/nt, ampicillin-resistant, and yst B-carrying strains) are prevalent in retail and processed meats in the study area, which provides valuable baseline data for food safety and public health safeguarding. Highlights: Yersinia spp. with different characteristics were prevalent in retail meat. Yersinia enterocolitica was the most commonly detected species. Yersinia enterocolitica biotype 1A isolates carried gene yst B and resisted multiple antibiotics. The genetic relationship of Yersinia isolates between pork, beef, and chicken was diverse.